2018
DOI: 10.2495/wp180111
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Adsorption Into the Fixed Bed Column From Drinking Groundwater

Abstract: One of the main goals of the World Health Organization (WHO) and its Member States is that "all people, regardless of their stage of development and their social-economic condition, have the right to have access to adequate drinking water". The problem of remediation of waters contaminated with toxic substances, using natural resources, is a special concern at a high level. Researchers' efforts have sought to find effective and cheap ways to reduce the impact on the environment. As(III) gets into the environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Based on experimental data obtained during preliminary attempts [34], the optimum conditions were established for synthesis of the desired composite material at different temperatures. So, when the synthesis was conducted at 45 °C, the reaction mass had to be stirred for 240 min (S2), at 55 °C the reaction mass had to be stirred for 45 min (S1), and at 58 °C the reaction mass had to be be stirred for 20 min (S3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on experimental data obtained during preliminary attempts [34], the optimum conditions were established for synthesis of the desired composite material at different temperatures. So, when the synthesis was conducted at 45 °C, the reaction mass had to be stirred for 240 min (S2), at 55 °C the reaction mass had to be stirred for 45 min (S1), and at 58 °C the reaction mass had to be be stirred for 20 min (S3).…”
Section: Resultsmentioning
confidence: 99%
“…These quantities of precursors were calculated in order to obtain a final ratio of Fe:C equal to 1:10. This ratio was chosen because the experimental data showed that the usage of higher quantities of iron chloride was not recommended because it leads to starch gelatinization, simultaneously it was proved that smaller ratio leads to a composite material with a lower efficiency in various applications [34].…”
Section: Methodsmentioning
confidence: 99%
“…As the contact time increases, the amount of adsorbate adsorbed to the adsorbent surface becomes higher until the equilibrium point is reached. Excessive contact time between adsorbent and adsorbate causes adsorbent to be saturated and detached from adsorbate [23][24][25].…”
Section: Sem/edx Analysismentioning
confidence: 99%